Exploration of Physics Concepts in Several Game Rides at Surabaya Prestasi Park - Dimas Ari Pratama; Alvin Khoirun Niza; Dwikoranto; Binar Kurnia Prahani (Indonesia Approach Education, 2022)
The purpose of this research is to find out the concept of physics in the game rides in Surabaya Prestasi Park and provide information through photos taken directly to readers. In this article the experimental method used is direct observation, documentation, and analysis (literature study) as a form of data collection. In this article, four physics concepts are found in the game rides, namely swings, slides, and seesaws in the form of simple harmonic motion concepts, energy, force, and levers. When playing swing there is a concept of physics that occurs in the motion of the swing, namely simple harmonic motion and the energy contained therein. In the slide there are physics concepts namely frictional force, energy concept and inclined plane. On the seesaw there is the concept of a lever. From this article it can be concluded that the rides at Surabaya Prestasi Park have a lot to do with physics concepts, including the concepts of simple harmonic motion, energy, force, and levers through personal documentation with direct observation so that apart from playing, children indirectly have learned the concept of physics so as to increase knowledge and insight